Persepsi Masyarakat Bajo Di Desa Samarengga Kecamatan Menui Kepulauan Kabupaten Morowali Terhadap Tingkat Pendidikan - Hikmah Labone; Nuraedah (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2021)
The problem in this research is (1) what factors influence related to the level of education. This study aims (1) to describe the influential factors related to the level of education in the Village Samarengga District Menui Kepulauan Kabupaten Morowali.This research uses qualitative descriptive type of research, the subjects in this research that the Villagers Samarengga District Menui Kepulauan Kabupaten Morowali, engineering data pemgumpulan using the method of observation, interview, documentation. The results of research in the analysis through data reduction, data presentation and data verification. The results showed (1) the factors that influence the perception of the society Bajo related to the level of education is the lack of awareness and lack of education that causes their education only up to primary school.